2018
DOI: 10.4103/jfmpc.jfmpc_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and cultural impact of tobacco in India

Abstract: Tobacco consumed either in the form of smoke or smokeless is hazardous to the human body. Death toll due to tobacco globally, has risen to about 6.4 million annually, and is on a constant increase. Since long, tobacco consumption has been attributed to a variety of factors including geographical variation, cultural factors and other associated variables. Earlier tobacco was considered as a taboo, but with advent of 21st century and commercialization of tobacco it has been prevalent among males and females. Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
2
11
0
Order By: Relevance
“…13,14 It can be explained as in India, tobacco use among females is still socially unacceptable in many cultures. 31 In the current study, tobacco use was found to be significantly associated with employment status as tobacco users were more likely to be employed compared to unemployed (p=0.005) and our finding is in line with previous study. 15 A possible explanation could be economic independence associated with employment attributing for the easier procurement of tobacco.…”
Section: Discussionsupporting
confidence: 92%
“…13,14 It can be explained as in India, tobacco use among females is still socially unacceptable in many cultures. 31 In the current study, tobacco use was found to be significantly associated with employment status as tobacco users were more likely to be employed compared to unemployed (p=0.005) and our finding is in line with previous study. 15 A possible explanation could be economic independence associated with employment attributing for the easier procurement of tobacco.…”
Section: Discussionsupporting
confidence: 92%
“…[ 15 17 ] In India, determinants of SLT use include wealth index, marginalized populations, such as scheduled tribe, peer pressure, lack of awareness, and misconceptions about SLT. [ 19 ] The inability to quit and chronic duration SLT use is associated with development of potentially malignant disorders of oral cavity leading to cancers of oral cavity, esophagus, and pancreas. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Being employed was associated with higher chances of tobacco use, as was observed in similar studies. While some studies report that unemployment was a predictor for tobacco use 20 , few analysed the various categories of occupations and their association with the forms of tobacco use 14,21 .…”
Section: Discussionmentioning
confidence: 99%